The Effects of Mentoring Functions on Career Adaptabilities and Career Self-Efficacy: the Role of Career Optimism - KANTEN, Selahattin; Assoc. Prof. Dr. Pelin KANTEN; Funda ÜLKER (European Journal of Multidisciplinary Studies, 2017)
This study aims to investigate the effects of mentoring functions on undergraduate student’s career adaptabilities and career self-efficacy levels and the mediating role of career optimism. It is suggested in the literature that some factors stimulate student’s career adaptability levels. Therefore, mentoring functions, career optimism and career self-efficacy are considered as predictors of career adaptabilities within the scope of the study. Accordingly, data which are collected by the survey method from 311 undergraduate students having an education on different field such as business administration, international trade and logistics, public management and labor economics are analyzed by using the structural equation modeling. The results of the study indicate that mentoring functions, which is labeled as role modeling, have significant effects on student’s career adaptability, career optimism and career self-efficacy levels. However, it has been observed that career optimism has a significant effect on career self-efficacy and career adaptabilities. On the other hand, it is seen that career optimism has a fully mediating role between the role modeling and career adaptabilities. In addition, career optimism has a fully mediating role between role modeling and career self-efficacy.
Keywords: Mentoring Functions, Career Adaptabilities, Career Self-Efficacy, Career Optimism